Residuality of imidacloprid in flowers of soursop (Annona muricata L.), papaya (Carica papaya Linnaeus) and Persian lemon (Citrus X latifolia Tanaka) (Scientia Agropecuaria, 2026)
The intensification of agriculture generates environmental pollution and affects the biodiversity of ecosystems. The use of imidacloprid is impacting the main natural pollinators of soursop, papaya, and lime crops. There are no records of the quantification and residual levels of imidacloprid in flowers, which is important for pollinating insects. The objective of this study was to determine the residual levels of imidacloprid in soursop, papaya, and Persian lime flowers in commercial, productive, and backyard orchards in central Veracruz, Mexico. Sampling was carried out in the tropical agroecosystem of central Veracruz, in the municipalities of Cotaxtla, Tlalixcoyan, and Medellín de Bravo; soursop flowers were sampled from backyard orchards, as well as open flowers in papaya and Persian lime orchards. For the determination and quantification of imidacloprid, the ELISA method was used with the imidacloprid detection kit. Concentrations in soursop flowers were 1.2 ng/ml, papaya 0.75 ng/ml, and Persian lime 0.65 ng/ml; high values of 0.85 ng/ml were found in flowers collected from orchards under conventional management. Imidacloprid concentrations in Persian lime, papaya, and soursop flowers pose a potential risk to natural pollinators. Exposure to imidacloprid can lead to mortality in the larvae and adults of species such as wild bees, which are important for crop production.
Keywords: Tropical fruit trees; neonicotinoids; contamination; pollinators; flowering